Potentiality of a Small and Fast Dense Plasma Focus as Hard X-Ray Source for Radiographic Applications - Pedreros, J (IOP PUBLISHING LTD, 2012)
Currently, a new generation of small plasma foci devices is being developed and researched, motivated by its potential use as portable sources of x-ray and neutron pulsed radiation for several applications. In this work, experimental results of the accumulated x-ray dose angular distribution and characterization of the x-ray source size are presented for a small and fast plasma focus device, PF-400J (880nF, 40nH, 27-29kV, 350J, T/4300ns). The experimental device is operated using hydrogen as the filling gas in a discharge region limited by a volume of around 80cm3. The x-ray radiation is monitored, shot by shot, using a scintillator-photomultiplier system located outside the vacuum chamber at 2.3m far away from the radiation emission region. The angular x-ray dose distribution measurement shows a well-defined emission cone, with an expansion angle of 5°, which is observed around the plasma focus device symmetry axis using TLD-100 crystals. The x-ray source size measurements are obtained using two image-forming aperture techniques: for both cases, one small (pinhole) and one large for the penumbral imaging. These results are in agreement with the drilling made by the energetic electron beam coming from the pinch region. Additionally, some examples of image radiographic applications are shown in order to highlight the real possibilities of the plasma focus device as a portable x-ray source. In the light of the obtained results and the scaling laws observed in plasma foci devices, we present a discussion on the potentiality and advantages of these devices as pulsed and safe sources of x-radiation for applications. © 2012 IOP Publishing Ltd.